Respuesta :

Answer:

1) Solution (2,-3)

2) Solution (-1, [tex]-\frac{3}{2}[/tex])

3) Solution ([tex]\mathbf{-\frac{1}{2},-\frac{5}{2}}[/tex])

Step-by-step explanation:

We need to solve equations using elimination

1) [tex]2x+2y=-2\\3x-2y=12[/tex]

Let:

[tex]2x+2y=-2--eq(1)\\3x-2y=12--eq(2)[/tex]

Adding both equations:

[tex]2x+2y=-2\\3x-2y=12\\--------\\5x=10\\x=\frac{10}{5}\\x=2[/tex]

We get value of x = 2

Now, put value of x into equation 1 to find value of y

[tex]2x+2y=-2\\Put\:x=2\\2(2)+2y=-2\\4+2y=-2\\2y=-2-4\\2y=-6\\y=-6/2\\y=-3[/tex]

So, we get y = -3

Solution (2,-3)

2) [tex]4x-2y=-1\\-4x+4y=-2[/tex]

Let:

[tex]4x-2y=-1--eq(1)\\-4x+4y=-2--eq(2)[/tex]

Adding both equations

[tex]4x-2y=-1\\-4x+4y=-2\\------\\2y=-3\\y=\frac{-3}{2}[/tex]

We get: y= -3/2

Now find value of x by putting value of y in eq(1)

[tex]4x-2y=-1\\Put\:y=\frac{-3}{2}\\4x-2( \frac{-3}{2})=-1\\4x+3=-1\\4x=-1-3\\4x=-4\\x=\frac{-4}{4}\\x=-1[/tex]

We get x = -1

Solution (-1, [tex]-\frac{3}{2}[/tex])

3) [tex]x-y=2\\x+y=-3[/tex]

let:

[tex]x-y=2--eq(1)\\x+y=-3--eq(2)[/tex]

Add both equations:

[tex]x-y=2\\x+y=-3\\-----\\2x=-1\\x=-\frac{1}{2}[/tex]

We get x = -1/2

Now, put value of x in equation 2

[tex]x+y=-3\\-\frac{1}{2}+y=-3\\y=-3+ \frac{1}{2}\\y=\frac{-6+1}{2}\\y=\frac{-5}{2}[/tex]

We get y = -5/2

Solution ([tex]\mathbf{-\frac{1}{2},-\frac{5}{2}}[/tex])